2007
DOI: 10.1248/cpb.55.422
|View full text |Cite
|
Sign up to set email alerts
|

Six New Triterpenoid Saponins from the Leaves of Ilex oblonga and Their Inhibitory Activities against TMV Replication

Abstract: Ilex (Aquifoliaceae) species are distributed widely in the People's Republic of China, and some are used extensively in folk medicine. For example, I. rotunda is an antipyretic and antidote and used for the treatment of the common cold, tonsillitis, and stomach and intestinal ulcers. I. pubescens is used for the treatment of coronary disease, myocardial infarction, dysentery, and erysipelas. I. cornuta and I. latifolia are used for the treatment of headache, toothache, bloodshot eyes, and tinnitus. Many report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Recently, a large number of natural glycosides were found to exhibit outstanding antiviral activities against TMV. [15][16][17][18][19][20][21] Moreover, a number of synthetic glycosides derivatives were found to exhibit antiviral activities against TMV. For example, Dai and co-workers synthesized a series of glycosides derivatives containing 1,5-diacetyl-2,4-dioxohexahydro-1,3,5-triazine moiety with good antiviral activity against TMV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of natural glycosides were found to exhibit outstanding antiviral activities against TMV. [15][16][17][18][19][20][21] Moreover, a number of synthetic glycosides derivatives were found to exhibit antiviral activities against TMV. For example, Dai and co-workers synthesized a series of glycosides derivatives containing 1,5-diacetyl-2,4-dioxohexahydro-1,3,5-triazine moiety with good antiviral activity against TMV.…”
Section: Introductionmentioning
confidence: 99%
“…According to the structures of the compounds, we had also found that with the same main structure, but with transformation of substituent groups, the anti-TMV activity of the compounds varied over a wide range [8], [9]. Here, the structure-activity relationship of 47 triterpenes and triterpenoid glycosides, isolated and purified from plants by our laboratory during the past years, most of which have initially been reported by us, were studied according to their anti-TMV activity against TMV replication in vivo by indirect ELISA.…”
Section: Introductionmentioning
confidence: 96%
“…Previous phytochemical studies on the barks and leaves of Ilex rotunda have resulted in the isolation of triterpenes [9], triterpene saponins [10,11], phenylpropanoids [12], and hemiterpene glycosides [13]. Triterpene saponins are commonly recognized as major constituents of the Ilex species and have been proven to be major active constituents closely related to the pharmacological cardiovascular protection activities [14,15,16,17]. Pedunculoside (PDC, Figure 1A), a triterpene saponin, is a representative and abundant component of Ilex rotunda [18,19].…”
Section: Introductionmentioning
confidence: 99%